Comparison of Silkworm Farming Business Income (Bombyx Mori L.) - Herawaty Herawaty; Andi Asikin Muchtar; Akrimah Akrimah; Nurul Muklisahah; Faizah Mahi (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2023)
South Sulawesi is still the largest producer of natural silk in Indonesia, although processing is still conventional. It is becoming an important trading center and an important non-timber forest product resource. This type of research is quantitative research, the data sources used are primary data and secondary data, with a population of silkworm rearing farmers located in Salojampu Village, Wajo Regency and Pising Village, Soppeng Regency. The results showed that silkworm farming in Salojampu Village, Wajo Regency, had the smallest income of Rp 183,667 per production cycle, while Pising Village, Soppeng Regency, had the largest income of Rp 311,333 per production cycle. Both farmer groups earned a total of IDR 495,000, with an average total income of IDR 247,500 per silkworm production cycle.